Characterizing Pressure‐Induced Uranium CH Agostic Bonds1. Issue 23 (16th April 2015) - Arnold, Polly L.; Prescimone, Alessandro; Farnaby, Joy H.; Mansell, Stephen M.; Parsons, Simon; Kaltsoyannis, Nikolas
Abstract: The diuranium(III) compound [UN′′2 ]2 (μ‐η 6 :η 6 ‐C6 H6 ) (N′′=N(SiMe3 )2 ) has been studied using variable, high‐pressure single‐crystal X‐ray crystallography, and density functional theory . In this compound, the low‐coordinate metal cations are coupled through π‐ and δ‐symmetric arene overlap and show close metalCH contacts with the flexible methyl CH groups of the sterically encumbered amido ligands. The metal–metal separation decreases with increasing pressure, but the most significant structural changes are to the close contacts between ligand CH bonds and the U centers. Although the interatomic distances are suggestive of agostic‐type interactions between the U and ligand peripheral CH groups, QTAIM (quantum theory of atoms‐in‐molecules) computational analysis suggests that there is no such interaction at ambient pressure. However, QTAIM and NBO analyses indicate that the interaction becomes agostic at 3.2 GPa. Abstract : Under pressure : Computational analyses and high‐pressure X‐ray crystallography are combined to study the U III compound [UN′′2 ]2 (μ‐η 6 :η 6 ‐C6 H6 ) (N′′=N(SiMe3 )2 ). With increasing pressure, the UU distances decrease and close contacts between the U and ligand CH groups become significantly shorter. Calculations suggest that the greater U⋅⋅⋅H interaction at high pressure can be classified as agostic.